Clinical significance of quantitative monitoring and mutational analysis of BCR-ABL1 transcript in Philadelphia chromosome positive B lymphoblastic leukemia. Issue 2 (1st February 2016) - Zhang, Linsheng; Ramjit, Ruan T.; Hill, Charles E.; Arellano, Martha; Khoury, H. Jean; Mann, Karen P.
Abstract : Quantitative detection of BCR-ABL1 transcript is essential in monitoring residual disease of Philadelphia chromosome positive B lymphoblastic leukemia (Ph+ B-LL). We studied the kinetics of BCR-ABL1 transcript in 41 Ph+ B-LL patients in correlation with their clinical outcome. A total of 23 patients achieved complete molecular remission at 6 months post-treatment. This was associated with a lower relapse risk and better overall survival. Likewise, sustainable complete molecular remission in 27 patients was associated with superior clinical outcome. Sporadic low level BCR-ABL1 was detected in 12 of 27 patients who had attained complete molecular remission. The relapse rate was significantly higher in non-transplant patients with persistent positive BCR-ABL1 than patients transplanted when BCR-ABL1 was detectable. All eight patients harboring ABL1 kinase domain mutations died of disease or were transferred to hospice care. We concluded that monitoring the level of BCR-ABL1 transcript after hematologic remission has predictive value to the long-term outcome.